Bioethanol: Is It a Suitable Biofuel for Hong Kong for Reducing Its Vehicular Emissions and Carbon Footprint?. (December 2017) - Leung, Dennis Y.C.; Yu, Laura C.; Lam, Gabriel C.K.; Kwok, Holly Y.H.; Cheng, W.K.
Abstract: Excessive vehicular emission is regarded as one of the main sources of air pollutants and this problem is especially serious in a metropolis such as Hong Kong. In California, legislation already exists to replace the toxic MTBE additive by an oxygenated additive such as ethanol. Many trials of testing ethanol fuel on gasoline fleet have also been conducted in many countries. In Hong Kong, the gasoline fuel practically contains no ethanol. In 2010, the Environment Bureau of the HKSAR Government has issued a climate change consultation document proposing 10% biofuels for road transport by 2020. Although the consultation document could not get through, whether Hong Kong can adopt the use of ethanol blended fuel and its environmental benefit is still an interesting and important issue in Hong Kong's environmental policy development. The purpose of this study is to evaluate the feasibility of introducing ethanol blended fuel to a metropolitan city such as Hong Kong. Implementing this policy involves a lot of difficulties related to infrastructure, taxation, acceptability of oil companies and car manufacturers, political issues etc. These issues have been addressed in this study. In addition, a life cycle analysis on the greenhouse gases emissions for different feedstock of ethanol production has been conducted to reveal the real benefit of using the fuel. Result indicated that ethanol produced locally from waste paper can generate real advantages to the Hong Kong environment and is more realistic in implementing in Hong Kong. There will be an insignificant cost penalty of 1% to 2% to motorists when using E5 and E10 respectively.